Determination of R Gene Composition in a Ctv Locus Conferring Citrus Tristeza Virus Resistance from the Genetic Resources of Citrus and Its Relatives - Jeong, Jiyeon; Woo, Jin-Kyu; Park, Young Chul; Park, Sukman; Yun, Su-Hyun; Lee, Yi; Cho, Gun-Hyoung; Song, Kwan Jeong; Kim, Ho Bang (Plant breeding and biotechnology, 2018)
Regardless of the importance of a viral pathogen, citrus tristeza virus (CTV), in citrus industry, molecular marker tools closely associated with its resistance trait have not been developed yet. Map-based cloning of a Ctv locus, one of at least two CTV-resistant loci, was previously reported from trifoliate orange. The genetic locus displayed a distinct feature of enriched composition of R genes that encode coiled-coil-nucleotide-binding site-leucine-rich repeat (CC-NBS-LRR) receptors. Based on the previous molecular characteristics of the genetic locus, we developed multiplex PCR marker sets to specifically detect seven R genes consisting of a Ctv locus. By using the multiplex PCR marker sets, we determined composition of seven R genes consisting of the genetic locus in a total of 155 citrus genetic resources including 12 of Korean landrace citrus. Genetic composition of seven R genes in the locus was variable among the genetic resources investigated. However, all of seven R genes were detected only in both trifoliate orange, Poncirus trifoliata and its derivative cultivar, P. trifoliata ‘Flying Dragon’, which have been reported to be resistant to CTV. Multiplex PCR marker sets established in this study would be an effective molecular tool to develop scion or rootstock cultivars with high resistance trait against CTV in citrus breeding program. KCI Citation Count: 3